Depression symptoms, HIV testing, linkage to ART, and viral suppression among women in a high HIV burden district in KwaZulu-Natal, South Africa: A cross-sectional household study. (March 2022) - Govender, Kaymarlin; Durevall, Dick; Cowden, Richard G; Beckett, Sean; Kharsany, Ayesha BM; Lewis, Lara; George, Gavin; Cawood, Cherie; Khanyile, David
Achieving the UNAIDS 90-90-90 targets by 2020 is contingent on identifying and addressing mental health challenges that may affect HIV testing and treatment-related behaviors. This study is based on survey data from KwaZulu-Natal, South Africa (2014–2015). HIV positive women who reported higher depression scores had a lower odds of having tested previously for HIV (15–25 years: AOR = 0.90, 95% CI [0.83, 0.98]; 26–49 years: AOR = 0.90, 95% CI [0.84, 0.96]). Because HIV testing behavior represents a gateway to treatment, the findings suggest mental health may be one challenge to attaining the UNAIDS 90-90-90 targets.